Evaluación de la historia clínica de pacientes caninos con signos clínicos compatibles con infección por neospora caninum, que asisten a consulta en la clínica veterinaria de la Universidad Antonio Nariño en Bogotá, Colombia (2019)
In Colombia there are few reports of seroprevalence of N. Caninum in canines, and those that do there are not very recent, hence the interest in carrying out a reference study that allows characterization of clinical histories in canine patients with related signs to infection by N. caninum, who attend consultation at the Veterinary Clinic of the Antonio Nariño University in Bogotá, Colombia; all this in order to highlight the possible health problems that it generates and also propose future solutions to the problem What does N. caninum infection represent at the public health level?